Agonist-selective signaling is determined by the receptor location within the membrane domains - Zheng, Hui; Chu, Ji; Qiu, Yu; Loh, Horace H; Law, Ping-Yee (Proceedings of the National Academy of Sciences - PNAS, 2008)
The basis for agonist-selective signaling was investigated by using the μ-opioid receptor (MOR) as a model. In the absence of agonist, MOR located within the lipid raft domains, whereas etorphine, but not morphine, induced the translocation of MOR from lipid raft to nonraft domains, similar to the action of methyl-β-cyclodextrin. The etorphine-induced MOR translocation required the dissociation of the receptor from Gαi2 first and then the binding of β-arrestin. In contrast, the low affinity of the morphine-MOR complex for β-arrestin and the rebinding of Gαi2 after GTP hydrolysis retained the complex within the lipid raft domains. Disruption of the MOR-Gαi2 interaction, either by deleting the ²⁷⁶RRITR²⁸⁰ sequence of MOR or knocking down the level of Gαi2, resulted in the translocation of MOR to the nonraft domains. In addition, lipid raft location of MOR was critical for G protein-dependent signaling, such as etorphine- and morphine-mediated inhibition of adenylyl cyclase activity and morphine-induced ERK phosphorylation, whereas β-arrestin-dependent, etorphine-induced ERK phosphorylation required MOR to translocate into the nonraft domains. Thus, agonist-selective signaling is regulated by the location of MOR, which is determined by interactions of MOR with G proteins and β-arrestin.